Phytotherapy of acute upper respiratory tract infections in children - Kundaković, Tatjana; Maksimović, Zoran (Archives of Pharmacy, 2022)
Acute upper respiratory tract infections (URIs) are the most common infections in the population, especially in children. URIs are mostly of viral origin and tend to resolve spontaneously in approximately one week. Bacterial URIs are less common, and come mostly as superinfections of acute viral diseases. The therapy is symptomatic and aimed at alleviating cough, maintaining the patency of airways and preventing disease progression. If there are no reasons to see a doctor, parents should be advised to apply general measures and give herbal medicinal products to their children, in an attempt to relieve cough, sore throat and nasal symptoms. In productive cough, herbal expectorants, such as, for example, Hederae helicis folium extracts, are used to facilitate the elimination of mucus. On the other hand, demulcents (Althaeae radix, Plantaginis lanceolatae folium) alleviate dry cough by reducing local irritation. Honey also significantly reduces the frequency and severity of acute cough episodes. Extracts of Sisymbrii officinalis herba and Pelargonii radix are useful for the alleviation of nasal symptoms and sore throat. If the application of the proposed herbal products does not resolve the symptoms within a week, advice of a medical doctor should be sought.